Bioactivities of isolated and synthetic riparins of Aniba riparia (NEES) MEZ (LAURACEAE): A brief review. (December 2022) - Barbosa, Cristina Rodrigues dos Santos; Bezerra, Antônio Henrique; Bezerra, Suieny Rodrigues; Macêdo, Nair Silva; Oliveira-Tintino, Cícera Datiane de Morais; Costa, José Galberto Martins da; Coutinho, Henrique Douglas Melo; dos Santos, Helcio Silva; Cunha, Francisco Assis Bezerra da
Abstract: Aniba riparia (Nees) Mez of the Lauraceae family, is a medicinal plant native to the Amazon region and commonly used as a spice. Chemical analyses carried out in 1982 on the leaves of A. riparia revealed the presence of a special group of alkamides called riparins. Subsequently, analogs were synthesized from isolated riparins. Studies have reported useful biological activities for pharmacological applications from natural and synthetic riparins, including anxiolytic, antidepressant, antinociceptive, myorelaxant, antioxidant, antiparasitic, cytotoxic, antitumor, anti-inflammatory, antifungal, and antibacterial activities against Gram-positive and Gram-negative bacteria. This review aims to coherently unify the data obtained from several studies on the bioactivities of natural and synthetic riparin molecules, highlighting recent advances in the understanding of these properties. Graphical Abstract: ga1 Highlights: Bioactivities of Riparins have been demonstrated by in vitro assays in animal models such as rodents. These activities have emphasis on anxiolytic, antidepressant, antinociceptive, and many other activities. Further studies are needed to understand the possible mechanisms of action of these molecules. Further studies are also necessary to address safety issues in order to develop possible pharmacological and therapeutic agents.